Insecticidal Potential of Two Monoterpenes against Tribolium Castaneum (Herbst.) and Sitophilus Oryzae (L.) Major Stored Product Insect Pests: Insecticidal Potential of Two Monoterpenes against Tribolium Castaneum (Herbst.) and Sitophilus Oryzae (L.) Major Stored Product Insect Pests - Brari, Jyotika (International Journal of Pharmaceutical & Biological Archive, 2020)
In the present study, two pure monoterpenes: Citronellol and geraniol were tested for their fumigant toxicity, repellent activity, and antifeedant activity against two stored product insect pests, Sitophilus oryzae (L.), and Tribolium castaneum (Herbst.) Monoterpenes tested showed varying degrees of toxicity against different species of stored product pests but were highly dependent on dosage and exposure duration. Geraniol was found to be highly effective against both S. oryzae and T. castaneum than citronellol. 0.02 μl/ml geraniol produced a mortality of 26.30 ± 0.11 after a short duration of 6 h that reached 52.76 ± 0.28% after an increased exposure of 72 h against S. oryzae while citronellol showed least activity producing a mortality of 52.76 ± 0.28 at 0.02 after 72 h of exposure. Similarly for T. castaneum geraniol produced 68.75 ± 0.55% mortality at 0.2 μl/ml after 72 h and citronellol even at a highest dose of 0.2 μl/ml caused 30.77 ± 0.49% mortality after 12 h. Geraniol produced 42.56 ± 1.9% repellent activity at 1 μl/cm2 after 1 h whereas repellency of 48.60 ± 1.4% was obtained by citronellol against T. castaneum after same concentration and time period citronellol and geraniol at a highest concentration of 1 μl/cm2 gave 56.61 ± 3.4 and 50.56 ± 1.1% repellency, respectively, after 5 h against S. oryzae. Feeding deterrence index (FDI) of 78.95 ± 0.09 and 67.59 ± 0.17% was obtained for citronellol and geraniol at a high concentration of 30 μl/g against T. castaneum. Citronellol showed 52.80 ± 0.32% FDI, followed by geraniol with 49.28 ± 0.17 FDI % against S. oryzae.